Extraction of ammonia from solutions with D2EHPA in three diluents: extraction equilibria and modeling. Issue 1 (6th April 2016) - Zhu, Xinyan; Chai, Wenshuai; Liu, Wei; Zhang, Weidong; Zhou, Zhiyong; Ren, Zhongqi
Abstract: Background: The extraction equilibria of ammonia was investigated with sodium salt of di‐(2‐ethylhexyl)phosphoric acid (D2EHPA) as extractant and kerosene, n ‐heptane and toluene as diluents at 298 ± 0.5 K. In addition, n ‐decanol was used as a modifier. Results: The distribution coefficient increases gradually with increasing Na–D2EHPA concentration in the organic phase. The equilibrium model for the extraction of ammonia with D2EHPA was established by utilizing the mass action law to determine model parameters and apparent extraction equilibrium constants ( K 1 and K 2 ). The combination of ion‐pair species of the type NH4 R(HR)4 and NH4 R is confirmed to exist in the organic phase at equilibrium. The calculated loadings of D2EHPA agree well with the experimental data. The distribution coefficient of ammonia decreases with increasing initial ammonium concentration in the aqueous solution. The effect of temperature on extraction equilibria was studied and the enthalpy change, free energy change and entropy change of the extraction process with D2EHPA in kerosene were obtained. Conclusions: Saponification of the extractant is necessary and benefits the extraction process. The model established in this work is valid in representing the equilibrium behavior of ammonia with D2EHPA in the three diluents. © 2016 Society of Chemical Industry